Union of Nizhny Novgorod Teachers of Religion: Creation and Activity (1902-1918) - N. E. Arkhipova (Научный диалог, 2020)
The activity of the first in Russia teachers of religion union of secondary educational institutions of Nizhny Novgorod (since 1915 - all Nizhny Novgorod teachers of religion) is considered. The relevance of the study is due to the revival of religious education in the modern school. The novelty of the study is that for the first time a generalized analysis of the work of the union, designed to rally the teachers of the “Law of God”, is presented, to facilitate the exchange of experience in order to increase the educational value of the course in the context of expanding secularization of public consciousness. It is concluded that the union carried out important work on the analysis of spiritual literature, textbooks, curricula, and sample lessons. It is shown that the lack of power and authority of the union deprived it of the opportunity to influence the choice of new teachers of religion and deputies for exams on the course “God’s Law”, limited its importance in solving the problems of religious and moral education of students. The author has come to the conclusion that the union, becoming an example for other cities, played a role in understanding the teaching theory and practice for harmonizing and optimizing the work of teachers of religion. It was established that in 1917-1918 the union took measures to preserve the institution of teaching of religion at school.